Natural Resources Potential of Northern Regions: Consistent Features of Comprehensive Assessment - Balashenko, Valery Vasilyevich; Ignatyeva, Margarita Nikolayevna; Loginov, Vladimir Grigoryevich (Economy of Regions, 2015)
The economic evaluation of renewable natural resources is the urgent and unsolved problem. Today, the assessment of natural resources is a priority for the national strategy of environmental management. In our country, a great influence on this process was provided by the development of market relations, causing the necessity to evaluate the natural resources potential. The state cadastral evaluation of natural resources is the basis for land tax, but it does not allow to assess comprehensively the natural resources potential. The article reveals the concept of economic evaluation, describes its implementation in the Northern regions. In the paper, the authors consider the traditional methodological approaches to the economic evaluation: cost and its modification, rent, market and alternative ones as well as the approaches based on the results of sociological research widely used lately. Also, the methodological approaches using the results of sociological research are utilized. For the assessment of the natural resources, the authors recommend the effective approaches that ensure the comparability calculations and improvement of the reliability of results. The proposed methodological approaches to the measurement of land, forestry, hunting, fishery and biological resources of wild plants allow to take into account the specific features of the Northern territories and implement a comprehensive economic assessment of natural resources potential of the territory. The authors consider the calculation of the unit value index of natural resources potential to rank the Northern territories of the Russian Federation according to the proportionality of project investment for development of natural resources. Methodological recommendations are approved for the conditions of the Berezovsky municipal region of Khanty-Mansi Autonomous Okrug - Yugra.